Model-based Testing of Cooperating Robotic Systems using Coloured Petri Nets - Lill, Raimar; Saglietti, Francesca (SAFECOMP 2013 - Workshop DECS (ERCIM/EWICS Workshop on Dependable Embedded and Cyber-physical Systems) of the 32nd International Conference on Computer Safety, Reliability and Security, 2013)
This article proposes a model-based testing approach for cooperating robotic systems. Coloured Petri Nets are used for capturing the high behavioural multiplicity of such systems in a compact and scalable way. For the purpose of systematically extracting test cases from underlying models, a number of coverage criteria based on different model entities is introduced. Finally, in order to ensure practicality, an incremental testing procedure based on increasingly refined coverage concepts is proposed. <br
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.lsinfs_1.modelb